Cochrane Database of Systematic Reviews 2005
DOI: 10.1002/14651858.cd004307.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Competitions and incentives for smoking cessation

Abstract: Incentives and competitions do not appear to enhance long-term cessation rates, with early success tending to dissipate when the rewards are no longer offered. Rewarding participation and compliance in contests and cessation programmes may have more potential to deliver higher absolute numbers of quitters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 71 publications
1
29
0
1
Order By: Relevance
“…Other studies have not found incentives to be effective; however, many of these studies are limited by small numbers of participants, cross-sectional designs, and/or very modest awards. 135 Traditionally, incentives have been directed toward providers of healthcare services through pay-for-performance programs. There is a growing consensus that incentives should be provided directly to the individual who is engaging in the behavior change.…”
Section: Financial Incentivesmentioning
confidence: 99%
“…Other studies have not found incentives to be effective; however, many of these studies are limited by small numbers of participants, cross-sectional designs, and/or very modest awards. 135 Traditionally, incentives have been directed toward providers of healthcare services through pay-for-performance programs. There is a growing consensus that incentives should be provided directly to the individual who is engaging in the behavior change.…”
Section: Financial Incentivesmentioning
confidence: 99%
“…All articles (15 reviews) that were published before 1 January 2004 were excluded from the review, because updates of earlier articles were available and articles on the same topics showed similar results. Seven of the remaining 24 articles (Ammendolia et al 2005;Hey and Perera 2005;Katz et al 2005;Novak et al 2007; Van der Molen et al 2005;Van Duijvenbode et al 2008) were included into the short descriptions of similar but possibly more relevant articles (Bos et al 2006;Engbers et al 2005;Matson-Koffman et al 2005;Moher et al 2005;Parks and Steelman 2008;Van Poppel et al 2004). That means that all in all 17 articles (19.8%) met the inclusion criteria, while 69 articles (80.2%) were excluded from the review.…”
Section: Study Selectionmentioning
confidence: 99%
“…Smedslund et al (2004) found a quit rate of around 18% in the intervention groups, but, as expected, the effect seemed to decrease over time and was not present beyond 12 months. [Note: Smedslund et al (2004) as well as Hey and Perera (2005) found that competitions and incentives are appropriate to improve participation rates in cessation programs, but not quit rates.] That means that the authors found evidence on the effectiveness of workplace smoking cessation programs at both 6-[Odds ratio (OR)=2.03] and 12-month follow-ups (OR=1.56 s.); however, the evidence level was not indicated.…”
Section: Smokingmentioning
confidence: 99%
“…Eine mögliche Fehlerquelle stellt der Anteil der Jugendlichen dar, der in der Follow-up-Befragung keine Auskunft über den Rauchstatus geben konnte oder wollte. Verschiedene Autoren empfehlen deswegen die Simulation eines Worst-Case-Szenarios [2,11,20]: Diesem Vorschlag folgend, haben wir angenommen, dass alle Personen der originalen Stichprobe, für die wegen Nichterreichbarkeit oder Teilnahmeverweigerung keine Angaben zur Abstinenz vorliegen, weitergeraucht haben. Damit wären 11,5% aller jugendlichen Teilnehmer zum Zeitpunkt der Nachbefragung und 7,3% kontinuierlich über 12 Monate abstinent gewesen.…”
Section: Alleinstellungsmerkmal Und Methodische Einschränkungenunclassified